Social Protection and Border Communities: A Critical Analysis of Policy Responses to Cross-Border Vulnerabilities in the Sahel Region - Timothy Sunday , Joshua; Chuks, Menyeneabasi, Franklin (African Journal of Stability and Development (AJSD), 2025)
The Sahel region has become a critical site for understanding the intersection of migration, vulnerability, and social protection in the context of fragility. Border communities in this region experience overlapping insecurities driven by climate shocks, conflict, and economic marginalisation, yet remain peripheral to national welfare frameworks. This study explores how social protection systems in Niger, Nigeria, Burkina Faso, and Mali respond to the specific needs of populations living in cross-border zones, marked by high mobility and informality. Using a mixed-methods design that integrates spatial vulnerability mapping, policy document analysis, and semi-structured interviews, the research interrogates the inclusiveness, coordination, and governance of social protection interventions at the border. Grounded in the theoretical perspectives of social risk management, transnational social protection, and social exclusion, the study reveals how state-centred welfare regimes often fail to account for the fluid livelihoods and identities of border populations. It argues for a re-conceptualisation of social protection as a transboundary public good that requires policy harmonisation and institutional collaboration across Sahelian states. The findings contribute to migration scholarship by highlighting how the governance of mobility intersects with welfare regimes, offering insights for building inclusive and resilient social protection systems in Africa’s borderlands.